Subjects of Disciplinary Proceedings Against a Judge under the Legislation of Ukraine and Spain: Comparative Legal Analysis - Bzova, Laura (Аналітично-порівняльне правознавство, 2025)
Disciplinary liability of judges is one of the key mechanisms of holding judges accountable. States are called upon to regulate this area, balancing two main interests – the need to ensure functional mechanisms of judicial accountability and to ensure real independence of judges. The main international legal instruments on the disciplinary liability of judges stipulate that states shall provide clear rules for which judges may be disciplined, excluding disciplinary liability for minor offences and for the interpretation of laws and facts. Disciplinary proceedings should either be conducted by an independent body. A proper disciplinary mechanism that holds all public officials accountable for misconduct is an important element of a credible justice system. At the same time, judicial discipline must be carefully balanced with the principle of judicial independence as a cornerstone of the rule of law. A miscarriage of justice that harms fundamental human rights and freedoms is not sufficient to hold a judge accountable. It must be attributed to the judge as a result of his or her performance of his or her functions in bad faith or through gross negligence. Judicial disciplinary responsibility is the control over the activities of judges and magistrates, a legal institution that exists in any state governed by the rule of law and benefits society and the state as a guarantor of the judiciary. Constitutional principles mean that violations and sanctions are predefined by law, so they can be imposed on judges and magistrates through a fair procedure and with all procedural guarantees. Beyond the substance of the institution, the Spanish and Ukrainian legal systems largely diverge in terms of infractions, sanctions and processing, despite some similarities in the administrative and judicial bodies involved. The accountability of judges and magistrates is considered a logical counterpoint to the independence of the judiciary, and in particular the irremovability of office. This article examines the accountability of judges and magistrates, both from an organic and a statutory perspective, as well as the irremovability of judges and its impact on the independence of the judiciary.
Keywords: disciplinary liability judge judicial system status of a judge High Council of Justice General Council of Judges